Digitalisasi dan Disparitas Pendidikan di Sekolah Dasar - Miftah, Zaini; Rozi, Fahru (IBTIDA', 2022)
Digitalization in education is essentially a government effort to uniform access to education and reduce the problem of digital inequality in the world of education. The purpose of this article is to identify aspects of the education digitization policy implemented at SDN Ngayung and the extent to which the digitalization policy can help SDN teachers improve access to education and participate in digitalization. The method used in this research is qualitative with a case study approach. The survey respondents in this study were six teachers, school principals and SDN supervisors. Data was collected through in-depth interviews and documentation. The survey found that SDN teachers in Ngayung village felt firsthand two aspects of the digitalization policy in education. The first is the digitization of education policy communications and the second is the digitization of learning. In the first dimension, teachers experience faster access to education policies. Teachers can better understand national education policies and follow direct instructions from the central government through available information channels. But for the second aspect, teachers are not ready in terms of content even though they are familiar with the media, they do not use various software products to maximize learning.